Artificial intelligence in marine ecosystem management: addressing climate threats to Kenya’s blue economy - Gesami, Brigid K.; Nunoo, Jacob (Frontiers in Marine Science, 2024)
This study investigates the application of Artificial Intelligence (AI) in monitoring and managing marine ecosystems to address the impacts of climate change on Kenya's Blue Economy. It aims to assess the threats posed by climate change to these ecosystems and explore the potential of AI solutions to enhance adaptation and resilience. The research employs a comprehensive review of secondary data sources, including academic publications, reports from reputable institutions, and other relevant materials. The study analyzes existing literature on AI applications in marine ecosystem management and climate change mitigation, focusing on the specific context of Kenya's Blue Economy. The study reveals that climate change poses significant threats to Kenya's marine ecosystems, including coral bleaching, ocean acidification, sea-level rise, and disruptions to ocean currents. AI technologies offer promising solutions for monitoring and managing these impacts, with applications in predictive modeling, resource optimization, and decision support. The research highlights the need for further exploration into specific AI applications tailored to Kenya's unique coastal challenges and the importance of incorporating diverse stakeholder perspectives. Additionally, it emphasizes the necessity for long-term impact assessments of AI technologies in the context of climate change mitigation. This study contributes to the growing body of knowledge on AI applications in environmental management, particularly within the context of Kenya's Blue Economy. By identifying the potential of AI to enhance resilience and sustainability in marine ecosystems, the research offers valuable insights for policymakers, researchers, and practitioners involved in climate change mitigation and adaptation efforts.